PENERAPAN METODE BERNYANYI UNTUK MENINGKATKAN DAYA INGAT ANAK PADA MATA PELAJARAN SKI DI KELAS III MI RAUDHLATUL ULUM KARANGPLOSO - Nilawati Nilawati; Mohammad Afifulloh; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
AbstractHistory Islamic culture is one of the religious lessons to know the development of Islam in the past. In studying the History of Islamic Culture more memorization. The learning process can affect the final results achieved by students. The singing method is an alternative way so that children quickly memorize and remember the material that has been taught. In the singing method can facilitate the teacher in the delivery of material, singing is a fun activity and loved by children so that children respond more quickly to lessons through singing. singing is a fun activity and is loved by children so that children respond faster to lessons through singing. The purpose of this study is to describe the effectiveness of children's memory in learning the History of Islamic Culture and the effectiveness of the bern method yanyi as an evaluation of students' memory. This study uses a qualitative approach. Procedure for collecting data using the observation method. after being given material with the singing method of Islamic Culture History, 83.88% was obtained. The conclusion of this study is that there is an increase in children's memory of Islamic Culture History subjects using the singing method.Keywords: Islamic Cultural History, Metode Singing, Children's Memory